Antibiotic resistance in hospital-acquired ESKAPE-E infections in low- and lower-middle-income countries: a systematic review and meta-analysis. Issue 1 (31st December 2022) - Ayobami, Olaniyi; Brinkwirth, Simon; Eckmanns, Tim; Markwart, Robby
ABSTRACT: Antimicrobial resistance (AMR) and hospital-acquired infections (HAIs) are global health challenges. The burden of antibiotic resistance in HAIs is still unclear in low- and lower-middle-income countries (L-LMICs). This study summarizes recent data on antibiotic resistance in priority HAIs (ESKAPE-E) in L-LMICs and compares them with data from high-income countries (HICs). EMBASE, Web of Science, and Global Index Medicus were searched for studies on AMR patterns in HAIs published from 01/2010 to 10/2020. Random-effects meta-analyses were performed to obtain pooled estimates. In total, 163 eligible studies were included in the review and meta-analysis. The pooled methicillin resistance proportion in Staphylococcus aureus was 48.4% (95% confidence interval [95%CI] 41·7-55·2, n = 80). Pooled carbapenem resistance proportions were high in Gram-negative pathogens: Escherichia coli : 16·6% (95%CI 10·7-23·4, n = 60); Klebsiella pneumoniae : 34·9% (95%CI 24·6-45·9, n = 50); Pseudomonas aeruginosa : 37.1% (95%CI 24·6-45·9, n = 56); Enterobacter spp.: 51·2% (95%CI 27·5-74·7, n = 7); and Acinetobacter baumannii (complex): 72·4% (95%CI 62·1-81·7%, n = 36). A higher resistance proportions were observed for third-generation cephalosporins: Klebsiella pneumoniae : 78·7% (95%CI 71·5-85·2, n = 46); Escherichia coli: 78·5% (95%CI 72·1-84·2%, n = 58); and Enterobacter spp.: 83·5% (95%CI 71·9-92·8, n = 8). We observed a high between-study heterogeneity (I 2  >  80%), which could not be explained by our set of moderators. Pooled resistance proportions for Gram-negative pathogens were higher in L-LMICs than regional and national estimates from HICs. Patients in resource-constrained regions are particularly affected by AMR. To combat the high resistance to critical antibiotics in L-LMICs, and bridge disparities in health, it is crucial to strengthen local surveillance and the health systems in general.